161k views
3 votes
For the graphed function f(x) = (2)x + 2 + 1, calculate the average rate of change from x = −1 to x = 0. a graph of an exponential function that goes through the points negative 2 comma 2, negative 1 comma 3, and 0 comma 5 −2 2 3 −3

2 Answers

6 votes

Answer:

2

Explanation:

i took it a couple weeks ago and can confirm its right

User Korteee
by
5.2k points
4 votes

Answer:

2 is the average rate of change of the function
f(x)=2^(x+2)+1 from
x=-1 to
x=0.

Explanation:

I assume you meant
f(x)=2^(x+2)+1 based off the points.

We are given that
(-1,3) and
(0,5) are points on this curve.

We are asked to find the average rate of change (the slope) from
x=-1 to
x=0.

We have the two points needed to find the slope.

We just need to line them up and subtract vertically then put 2nd difference on top of 1st difference.


(-1,3)


(0,5)

--------------------Subtracting!


-1,-2

So the slope is
(-2)/(-1)=2.

User ChrisCrossCrash
by
5.8k points